2016
DOI: 10.1007/s10926-016-9660-3
|View full text |Cite
|
Sign up to set email alerts
|

Researching Complex and Multi-Level Workplace Factors Affecting Disability and Prolonged Sickness Absence

Abstract: Purpose There is growing research evidence that workplace factors influence disability outcomes, but these variables reflect a variety of stakeholder perspectives, measurement tools, and methodologies. The goal of this article is to summarize existing research of workplace factors in relation to disability, compare this with employer discourse in the grey literature, and recommend future research priorities. Methods The authors participated in a year-long collaboration that ultimately led to an invited 3-day c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 79 publications
1
36
0
13
Order By: Relevance
“…Previous analyses of the role of the workplace in enhancing RTW outcomes have identified a range of contributing factors, such as the perspective held of the workplace by the injured workers [23], features of the workplace and its responsiveness to the injured worker [24], and the need to accommodate the differing interests held by the range of stakeholders who are involved [25] (see accompanying articles on workplace factors and interventions [26, 27]). Achieving a successful RTW is likely therefore to require workplace changes at several levels.…”
Section: Workplace-focused Interventions: the Case Of Musculoskeletalmentioning
confidence: 99%
“…Previous analyses of the role of the workplace in enhancing RTW outcomes have identified a range of contributing factors, such as the perspective held of the workplace by the injured workers [23], features of the workplace and its responsiveness to the injured worker [24], and the need to accommodate the differing interests held by the range of stakeholders who are involved [25] (see accompanying articles on workplace factors and interventions [26, 27]). Achieving a successful RTW is likely therefore to require workplace changes at several levels.…”
Section: Workplace-focused Interventions: the Case Of Musculoskeletalmentioning
confidence: 99%
“…In particular, growing evidence suggests that workplace factors affect employment outcomes for people with disabilities (Kristman et al 2016). Research has shown that receipt of workplace accommodations is associated with better employment outcomes (Burkhauser et al 1995;Chow 2012;Cook et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Kristman et coll. 12 identifient dans leur revue de littérature quatre modèles sur lesquels s'appuient les employeurs et gestionnaires pour prendre des décisions concernant la gestion des absences du travail et de l'incapacité au travail. Il s'agit des modèles : 1) biomédical ; 2) de gestion financière ; 3) de gestion du personnel ; et 4) de développement organisationnel.…”
unclassified
“…Quant au modèle fondé sur la gestion financière, en lien aussi avec la philosophie adoptée par les compagnies d'assurance, il est basé sur la prudence et le moindre risque, notamment lorsqu'il s'agit de prendre des décisions qui engendrent des coûts monétaires pour l'organisation 12 . Les stratégies mises en avant sont celles qui engendrent les moindres coûts avec le souci d'éviter toute responsabilité chez les gestionnaires des organisations.…”
unclassified
See 1 more Smart Citation